Rhyw Fath o Ynfytyn - Roberts, Lleucu (Y Lolfa, 2012)
A bold novel about strong characters who are threatened by the shadows of their past. They will have to face them eventually, though this will shake them forever. Intro – UN – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – 10 – 11 – 12 – 13 – 14 – 15 – 16 – 17 – DAU – 18 – 19 – 20 – 21 – 22 – 23 – 24 – 25 – 26 – 27 – 28 – 29 – 30 – TRI – 31 – 32 – 33 – 34 – 35.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books